Effect of the acid degradation on the properties of polyester reinforced with glass fibers - Lara-González, Luis Ángel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
The current article focuses on evaluating the effect of the half acid degradation in the mechanical and other properties and in the structural integrity of a polyester fiber-reinforced glass in two different orientation types:Mat, in taffeta and multiaxial fabrics, after the immersion process in nitric acid to 5 % of volume.